CRISPR-Cas9-based mutagenesis frequently provokes on-target mRNA misregulation - Rubina Tuladhar (Nature Portfolio, 2019)
CRISPR-Cas9 genome editing is presumed to knock out gene function by generating a frameshift during NHEJ repair. Here, the authors investigate mRNA and protein expression in edited lines and find genome editing can generate internal ribosome entry sites or alternatively spliced variants.